Coagulation, fibrinolytic parameters and cytokines response to weight reduction in obese Saudi women - Abd El-Kader, Shehab Mahmoud; Refaey, Neveen; Atiaa, Amany (J Med Rehab Sci, 2025)
Background: Obesity is a relevant risk factor for major cardiovascular events due to the atherosclerotic involvement of coronary, cerebral and lower limb arterial vessels. A major role in the increased cardiovascular risk is played by platelets, which show an increased activation and a reduced sensitivity to the physiological and pharmacological anti-aggregating agents. However, no studies have been conducted to compare the effects of simple calorie restriction and those of calorie restriction combined with aerobic exercise on fibrinolytic, coagulative factors and cytokines. Objective: The aim of this study was to investigate the effect of weight reduction on the fibrinolytic, coagulative factors and cytokines in obese Saudi women. Material and Methods: One hundred obese Saudi women participated in this study, and were included into two equal groups. The first group (A) received physical training combined with dietary measures, three sessions per week for three months. The second group (B) received no treatment intervention. Measurements of body mass index (BMI), Fibrinogen, von Willbrand factor (vWF-Ag) antigen, plasminogen activator inhibitor-1 activity (PAI-1:Ac) and antigen (PAI-1:Ag) & prothrombin time (PT), partial thromboplastin time (PTT), tissue plasminogen activator activity (tPA:Ac) , antigen (tPA:Ag) , tumor necrotic factor - alpha (TNF-α), interleukin–6 (IL-6) and leptin were done before the study and after three weeks at the end of the study. Results: The results of this study indicated a great significant decrease in BMI, Fibrinogen, vWF-Ag, PAI-1:Ac and PAI-1:Ag & PT, PTT, tPA:Ac, tPA:Ag ,TNF-α, IL-6 and leptin in group (A), while these changes were not significant in group (B). Conclusion: Weight reduction modulates Coagulation, fibrinolytic parameters and cytokines in obese Saudi women.